PERBEDAAN HASIL BELAJAR SISWA MODEL MIND MAPPING DENGAN MODEL STUDENTS FACILITATOR AND EXPLAINING PADA MATERI EKOSISTEM KELAS VII SMP NEGERI 1 DABO SINGKEP - Dahrul Aman Harahap; Lani Puspita; Ermi Juriani (SIMBIOSA, 2014)
The purposes of this research to know the significant differences in the learning outcome by using Mind Mapping (X1) and Student Facilitator and Explaining (X2) on ecosystem material. Population in the research are 161 students and the researcher takes two sample of five classes. There are  VII.3 as Mind Mapping class and VII. 5 as Student Facilitator and Explaining class. That use to experiment classes. Data collected using a multiple choice test which consists of 25 question. This research uses T-test  according to data analysis 4.62 2.00 (α) 0.05. it means zero hypothesis (HO) refused and the alternative hypothesis is accepted (HI)  finally the research found that it has significant differences of the student’s learning outcome by using Mind Mapping and Student Facilitator and Explaining on ecosystem material at class in VII SMP Negeri 1 Dabo Singkep school 2013 / 2014 year.